2017
DOI: 10.1093/annonc/mdx266
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte density determined by computational pathology validated as a predictor of response to neoadjuvant chemotherapy in breast cancer: secondary analysis of the ARTemis trial

Abstract: BackgroundWe have previously shown lymphocyte density, measured using computational pathology, is associated with pathological complete response (pCR) in breast cancer. The clinical validity of this finding in independent studies, among patients receiving different chemotherapy, is unknown.Patients and methodsThe ARTemis trial randomly assigned 800 women with early stage breast cancer between May 2009 and January 2013 to three cycles of docetaxel, followed by three cycles of fluorouracil, epirubicin and cyclop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
24
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 14 publications
7
24
2
2
Order By: Relevance
“…Following this, it is possible to generate predictive or prognostic assays by applying traditional statistical frameworks (eg, Cox regression models) or machine learning classifiers of the digital pathology features to find associations to ground truth labels (eg, clinical and survival endpoints, or tissue-type classification). The Cambridge group has recently reported results using digitized pretreatment tumor biopsies and post-treatment surgical specimens obtained from the ARTemis trial [22] and from the Neo-tAnGo trial [23]. The primary aim of those studies was to investigate pathomic markers of NAC response in breast cancer, which included 1,223 baseline samples.…”
Section: Pathomics: Machine Learning Applications In Breast Oncologymentioning
confidence: 99%
See 2 more Smart Citations
“…Following this, it is possible to generate predictive or prognostic assays by applying traditional statistical frameworks (eg, Cox regression models) or machine learning classifiers of the digital pathology features to find associations to ground truth labels (eg, clinical and survival endpoints, or tissue-type classification). The Cambridge group has recently reported results using digitized pretreatment tumor biopsies and post-treatment surgical specimens obtained from the ARTemis trial [22] and from the Neo-tAnGo trial [23]. The primary aim of those studies was to investigate pathomic markers of NAC response in breast cancer, which included 1,223 baseline samples.…”
Section: Pathomics: Machine Learning Applications In Breast Oncologymentioning
confidence: 99%
“…The primary aim of those studies was to investigate pathomic markers of NAC response in breast cancer, which included 1,223 baseline samples. Machine learning algorithms using a k-NN and support vector machine learning was used to classify tumor, stroma, and lymphocytes of the digitized pathology samples [22,23]. The results showed that lymphocyte density, as measured in the pre-treatment biopsy, was an independent predictor of pathological complete response (pCR); defined as a complete disappearance of invasive cancer cells after treatment (odds ratio ¼ 2.92-4.46, P < .001) [22].…”
Section: Pathomics: Machine Learning Applications In Breast Oncologymentioning
confidence: 99%
See 1 more Smart Citation
“…7 Moreover, cell densities of lymphocytes, macrophages and dendritic cells have also been shown to be prognostic in breast, ovarian and lung cancer without restricting analyses to malignant epithelial cell areas. [8][9][10] Approaches that combine analyses of multiple immune infiltrates, such as the CD3/CD8 immunoscore in colorectal cancer, 11 have not yet been developed for ovarian cancer prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…[52]. Auch in anderen Studien konnte der Zusammenhang von TILs mit dem Ansprechen auf eine neoadjuvante Chemotherapie gezeigt werden [53][54][55]. In einigen Studien in der adjuvanten Therapiesituation konnte ebenfalls ein prognostischer Effekt gezeigt werden [56].…”
Section: Chemotherapie Oder Keine Chemotherapie -Bestimmung Molekularunclassified